Demystifying the leadership kaleidoscope into an integrated view. Issue 7 (14th August 2017) - Marathe, Gaurav; Balasubramanian, Girish; Singhal, Manish
Abstract : Purpose: The purpose of this paper is to argue for theoretical integration as a major step in consolidation of the vast leadership literature. It is an attempt to lay out a basic canvas that could be further used for building an integrated theory of leadership. Design/methodology/approach: The concept matrix framework (Webster and Watson, 2002) has been used for analytical abstraction to organize the published research on leadership and distill certain commonalities. The paper finally proposes certain pivots for theoretical integration of the leadership literature. Findings: A thorough analysis of the leadership literature and the identification of commonalities within the various theories help the authors to identify the change and collective filter, outcomes of leadership, organizational outcomes, leadership role, sources of leadership, processes within the larger leadership process and the context as the pivots for building an integrated theory of leadership. Research limitations/implications: While the paper is not a detailed literature review and lacks predictive power, it is a synthesis of the published literature. The paper proposes a descriptive model meant to provide a sound foundation for an integrated theory of leadership. Practical implications: The paper provides a framework to reduce the complexity and ambiguity of leadership research literature and could be utilized as a starting platform for an integrated theory of leadership. It is hoped that this shall also provide leaders and leadership training providers with a more holistic approach for leadership assessment and development. Originality/value: Based on a survey of literature, the explanation of the leadership process, suggestions for evaluation of quality of leadership and pivots for theoretical integration are the main contributions.